Targeted medical nutrition for cachexia in chronic obstructive pulmonary disease: a randomized, controlled trial. Issue 1 (10th September 2017) - Calder, Philip C.; Laviano, Alessandro; Lonnqvist, Fredrik; Muscaritoli, Maurizio; Öhlander, Maria; Schols, Annemie
Abstract: Background: Cachectic patients with chronic obstructive pulmonary disease (COPD) may benefit from nutritional support. This double‐blind, randomized, controlled trial evaluated the safety and efficacy of targeted medical nutrition (TMN) vs. an isocaloric comparator in pre‐cachectic and cachectic patients with COPD. Methods: Patients aged ≥50 years with moderate‐to‐severe COPD and involuntary weight loss or low body mass index (16–18 kg/m 2 ) were randomized 1:1 to receive TMN ( 230 kcal; 2 g omega‐3 fatty acids; 10 μg 25‐hydroxy‐vitamin D3) or isocaloric comparator twice daily for 12 weeks (ClinicalTrials.gov Identifier: NCT02442908). Primary safety endpoints comprised adverse events and changes in vital signs, laboratory parameters, and concomitant medications. Secondary efficacy endpoints included changes in weight, body composition, exercise tolerance, metabolic biomarkers, and systemic inflammation. Results: Forty‐five patients were randomized to receive TMN ( n = 22; mean 69.2 years) or isocaloric comparator ( n = 23; mean 69.7 years). TMN was well tolerated. Adverse events were similar in number and type in both groups. Compliance to both products was good (TMN, 79%; comparator, 77%). Both groups gained weight, but the TMN group gained comparatively more fat mass ( P = 0.0013). Reductions in systolic blood pressure ( P = 0.0418) and secondary endpoints of triglycerides ( P = 0.0217) and exercise‐induced fatigue ( P = 0.0223) and dyspnoea ( P = 0.0382), and increases in high‐density lipoprotein cholesterol ( P = 0.0254), were observed in the TMN vs. the comparator group by week 12. Conclusions: Targeted medical nutrition containing high‐dose omega‐3 fatty acids, vitamin D, and high‐quality protein is well tolerated with a good safety profile and has positive effects on blood pressure and blood lipids and on exercise‐induced fatigue and dyspnoea. Therefore, this TMN could be clinically beneficial in the nutritional and metabolic support of pre‐cachectic and cachectic patients with COPD.